4‐Hydroxybenzoic acid is a diffusible factor that connects metabolic shikimate pathway to the biosynthesis of a unique antifungal metabolite in Lysobacter enzymogenes. Issue 1 (15th February 2017) - Su, Zhenhe; Chen, Hongfu; Wang, Ping; Tombosa, Simon; Du, Liangcheng; Han, Yong; Shen, Yuemao; Qian, Guoliang; Liu, Fengquan
Summary: Heat‐stable antifungal factor (HSAF) produced by Lysobacter enzymogenes is a potential lead compound for developing new antibiotics. Yet, how L. enzymogenes regulates the HSAF biosynthesis remains largely unknown. Here, we show that 4‐hydroxybenzoic acid (4‐HBA) serves as a diffusible factor for regulating HSAF biosynthesis. The biosynthesis of 4‐HBA involved an oxygenase, LenB2, and mutation of lenB2 almost completely abolished 4‐HBA production, leading to significantly impaired HSAF production. Introduction of a heterologous gene coding for 4‐HBA biosynthetic enzyme into the lenB2 mutant restored the production of 4‐HBA and HSAF to their corresponding wild‐type levels. Exogenous addition of 0.5–1 μM 4‐HBA was sufficient to restore HSAF production in the lenB2 mutant. Furthermore, the shikimate pathway was found to regulate the biosynthesis of HSAF via 4‐HBA. Finally, we identified a LysR‐family transcription factor (LysRLe ) with activity directed to HSAF production. LysRLe could bind to the HSAF promoter and, as a result, regulates expression of HSAF biosynthesis genes. The 4‐HBA could bind to LysRLe and appeared to partly enhance formation of the LysRLe –DNA complex. Collectively, our findings suggest that L. enzymogenes produces 4‐HBA to serve as an adaptor molecule to link the shikimate pathway to the biosynthesis of a unique antifungal metabolite (HSAF). Abstract : LenB2 utilizes chorismate from the shikimate pathway as the substrate to produce 4‐HBA and 3‐HBA. HSAF production requires 4‐HBA. LysRLe is a transcription factor that could bind the HSAF promoter (pHSAF), as a result, regulates expression of HSAF biosynthesis genes and HSAF production. 4‐HBA could directly interact with LysRLe, and appears to partly promote the binding of LysRLe to the HSAF promoter in vitro. The chemical structure of HSAF was indicated by the symbol ## (Yu et al ., 2007 ; Xu et al ., 2015 ). Moreover, 3‐HBA is thought to involve in producing the Lysobacter pigments (one structure was indicated by #) via the characterized pigment biosynthetic cluster (Wang et al ., 2013 ), which was most probably similar to that of X. campestris (Zhou et al ., 2013a ). IM: inner membrane; OM: outer membrane.